Salience driven attention is pivotal to understanding others' intentions. Issue 1 (2nd January 2021) - Rijpma, Myrthe G.; Shdo, Suzanne M.; Shany-Ur, Tal; Toller, Gianina; Kramer, Joel H.; Miller, Bruce L.; Rankin, Katherine P.
ABSTRACT: Interpreting others' beliefs, desires and intentions is known as "theory of mind" (ToM), and is often evaluated using simplified measurement tools, which may not correctly reflect the brain circuits that are required for real-life ToM functioning. We aimed to identify the brain structures necessary to correctly infer intentions from realistic scenarios by administering The Awareness of Social Inference Test, Enriched subtest to 47 patients with behavioural variant frontotemporal dementia, 24 patients with progressive supranuclear palsy syndrome, 31 patients with Alzheimer's syndrome, and 77 older healthy controls. Neuroimaging data was analyzed using voxel based morphometry, and participants' understanding of intentions was correlated with voxel-wise and region-of interest data. We found that structural integrity of the cinguloinsular cortex in the salience network (SN) was more pivotal for accurate ToM than previously described, emphasizing the importance of the SN for selectively recognizing and attending to social cues during ToM inferences.